The implementation of business policies of use and control of technological work tools as an effective mechanism to suspend the expectation of confidentiality in the employment relationship - Alva Cruz, Josselyn Estefanía (2017)
Based on the considerations presented by the Constitutional Court in the light of a specific case, this article addresses the discussion about the limit of intervention that the employer has to intercept and collect those communications that are protected by the secrecy of the law of the Communications of workers, establishing the possibility of implementing new control mechanisms that suspend any kind of expectation of confidentiality.